THE EXPERIMENTAL REQUIREMENTS FOR QUANTITATIVE MEASUREMENT OF CARRIER RECOMBINATION AT DEFECTS IN SEMICONDUCTORS USING THE EBIC TECHNIQUE - Wilshaw, P (1989)
An analysis is made of the experimental parameters which can cause errors when EBIC measurements are used to investigate the recombination behaviour of defects. In the first part of the paper specimen effects such as the minority carrier diffusion length and depletion region width are considered. In the second an analysis is made of how EBIC signal measurements depend on the electrical properties of the collecting junction, the series resistance of the circuit and the size of the induced current. It is shown that provided the induced current remains smaller than the diode saturation current, EBIC contrast measurements are independent of the value of the series resistance. Thus it is deduced that accurate EBIC contrast measurements can, under certain conditions, be made even when very large series resistances are present. Other conditions are identified for which EBIC measurements will be in error. Experimental results are presented which verify the behaviour deduced by the analysis used for signal collection.